Comment on "Incipient plasticity of diamond during nanoindentation" by C. Xu, C. Liu and H. Wang, RSC Advances, 2017, 7, 36093 - Goel, Saurav; Stukowski, Alexander (Royal Society of Chemistry, 2018)
A recent molecular dynamics simulation study on nanoindentation of diamond carried out by Xu et al. 1 has reported observation of the presence of a controversial hexagonal lonsdaleite phase of carbon in the indentation area. In this comment, we question the reported observation and attribute this anomaly to shortcomings of the long range bond order potential (LCBOP) employed in the nanoindentation study.